Prospective cohort studies of dietary vitamin B6 intake and risk of cause-specific mortality. Issue 3 (June 2019) - Zhao, Long-Gang; Shu, Xiao-Ou; Li, Hong-Lan; Gao, Jing; Han, Li-Hua; Wang, Jing; Fang, Jie; Gao, Yu-Tang; Zheng, Wei; Xiang, Yong-Bing
Summary: Background & aims: Vitamin B6 has been postulated to play an important role in determining chronic diseases. However, few studies have evaluated associations between dietary vitamin B6 and cause-specific mortality comprehensively. Methods: We investigated the associations between vitamin B6 from diet and risk of all-cause, and cause-specific mortality in 134, 480 participants from the Shanghai Men's Health Study (2002–2014) and Shanghai Women's Health Study (1997–2014). The median follow-up periods for men and women were 10.3 and 16.2 years, respectively. We estimated hazard ratio (HR) and 95% confidence interval (CI) using Cox proportional hazards models. Results: After adjustment for suspected confounders, the multivariable-adjusted HRs for the highest versus lowest quintiles for total, CVD, stroke and CHD mortality among men were 0.83 (95%CI = 0.76, 0.90), 0.73 (95%CI = 0.63, 0.85), 0.71 (95%CI = 0.58, 0.88), 0.66 (95%CI = 0.47, 0.91), accordingly. Women with the highest intake had significantly 17% (HR = 0.83; 95% CI = 0.77, 0.90), 20% (HR = 0.80; 95% CI = 0.70, 0.92), and 28% (HR = 0.72; 95% CI = 0.59, 0.86) lower risks of total, CVD and stroke mortality compared with those of women with lowest vitamin B6 intake. No significant association was observed between dietary vitamin B6 and cancer mortality both among men and women. Conclusions: In the current study with two prospective Chinese cohorts, high dietary vitamin B6 consumption was inversely associated with risk of all-cause and CVD mortality. Highlights: Dietary vitamin B6 was inversely associated with all-cause mortality in China. These associations were also found for cardiovascular disease mortality. Dietary vitamin B6 might not be associated with cancer mortality risk.